1H MR spectroscopic imaging of the prostate at 7T using spectral‐spatial pulses. Issue 3 (6th May 2015) - Lagemaat, Miriam W.; Breukels, Vincent; Vos, Eline K.; Kerr, Adam B.; van Uden, Mark J.; Orzada, Stephan; Bitz, Andreas K.; Maas, Marnix C.; Scheenen, Tom W.J.
Abstract : Purpose: To assess the feasibility of prostate 1 H MR spectroscopic imaging (MRSI) using low‐power spectral‐spatial (SPSP) pulses at 7T, exploiting accurate spectral selection and spatial selectivity simultaneously. Methods: A double spin‐echo sequence was equipped with SPSP refocusing pulses with a spectral selectivity of 1 ppm. Three‐dimensional prostate 1 H‐MRSI at 7T was performed with the SPSP‐MRSI sequence using an 8‐channel transmit array coil and an endorectal receive coil in three patients with prostate cancer and in one healthy subject. No additional water or lipid suppression pulses were used. Results: Prostate 1 H‐MRSI could be obtained well within specific absorption rate (SAR) limits in a clinically feasible time (10 min). Next to the common citrate signals, the prostate spectra exhibited high spermine signals concealing creatine and sometimes also choline. Residual lipid signals were observed at the edges of the prostate because of limitations in spectral and spatial selectivity. Conclusion: It is possible to perform prostate 1 H‐MRSI at 7T with a SPSP‐MRSI sequence while using separate transmit and receive coils. This low‐SAR MRSI concept provides the opportunity to increase spatial resolution of MRSI within reasonable scan times. Magn Reson Med 75:933–945, 2016. © 2015 Wiley Periodicals, Inc.